A simple but sensitive and efficient fluorescent probe for "turn-on" sensing of ClO−. (15th July 2020) - Yang, Xiaofeng; Shi, Wendi; Dong, Xiaoling; Cui, Chuanyang; Huang, Xin; Wang, Xue; Xie, Hangxin; Li, Yexin; Yan, Mei; Cui, Yu; Sun, Guoxin
Graphical abstract: A simple but sensitive and efficient "turn-on" benzothiazole-based fluorescent probe YXF for ClO − detection was developed. Compared with previous fluorescent probes, the main advantages of this probe were a rapid response time (within 5 s), a low detection limit (1.8 × 10 −8 M), a high selectivity and an excellent sensitivity. Highlights: A simple "turn-on" benzothiazole-based fluorescent probe for ClO − . A rapid-response time within 5 s for detection ClO − . A low detection limit of 1.8 × 10 −8 M for ClO − . High selectivity and sensitivity for ClO − . Abstract: A simple but sensitive and efficient fluorescent probe YXF for "turn-on" detecting ClO − had been developed. For compound YXF, the benzothiazole unit was the efficient fluorophore, and the CN unit was the recognition site for ClO − . It could detect ClO − with a high selectivity and sensitivity over other 29 kinds of common analytes including some reactive oxygen molecules. After addition of 30 equiv. NaClO to the solution of YXF, the fluorescent intensity at 452 nm enhanced with an approximately 37-fold within seconds. The fluorescence intensity of the reaction between YXF and NaClO showed a good linearity in the NaClO concentration range of 1–180 μM and YXF had a low detection limit of 1.8 × 10 −8 M. In addition, NaClO-promoted oxidation cleavage of CN unit of probe YXF was verified by HR-MS and NMR spectrometry analysis. Moreover, probe YXF could be successfully applied for detection of ClO − concentration in several tap water and 84 disinfectant samples.